The Psychology of Silicon Valley Ethical Threats and Emotional Unintelligence in the Tech Industry - Cook, Katy (Springer Nature, 2020)
Misinformation. Job displacement. Information overload. Economic inequality. Digital addiction. The breakdown of democracy, civility, and truth itself. This open access book explores the conscious and unconscious norms, values, and characteristics that drive behaviors within the high-tech capital of the world, Silicon Valley, and the sector it represents. In an era where the reach and influence of a single industry has the potential to define the future of our world, it has become apparent just how little we know about the organizations driving these changes. The Psychology of Silicon Valley offers a revealing look inside the mind of world's most influential industry and how the identity, culture, myths, and motivations of Big Tech are harming society. The book argues that the bad values and lack of emotional intelligence borne in the vacuum of Silicon Valley will have lasting consequences on everything from social equality to the future of work to our collective mental health. Katy Cook expertly walks us through the psychological landscape of Silicon Valley, including its leadership, ethical, and cultural problems, and artfully explains why we cannot afford to ignore the psychology and values that are behind our technology any longer.